2013
DOI: 10.1103/physrevc.87.065502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the density-dependent weak form factors on the neutrino reaction via neutral current for the nucleon in nuclear matter and12C

Abstract: Effects of the density-dependent weak form factors on the neutrino reaction via neutral current for the nucleon in nuclear matter and ¹²C Physical Review C, 2013; 87(6) 3. The right to use all or part of the Article, including the APS-prepared version without revision or modification, on the author(s)' web home page or employer's website and to make copies of all or part of the Article, including the APS-prepared version without revision or modification, for the author(s)' and/or the employer's use for educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…[89][90][91][92][93][94][95][96][97]. In the earlier works of neutrino-nucleus interaction [98,99], the in-medium modifications of only the nucleon weak form factors were applied, but both effects of the in-medium weak and EM form factors were studied in Refs. [37,38].…”
Section: Medium Modifications Of the Nucleon Electroweak Form Factorsmentioning
confidence: 99%
“…[89][90][91][92][93][94][95][96][97]. In the earlier works of neutrino-nucleus interaction [98,99], the in-medium modifications of only the nucleon weak form factors were applied, but both effects of the in-medium weak and EM form factors were studied in Refs. [37,38].…”
Section: Medium Modifications Of the Nucleon Electroweak Form Factorsmentioning
confidence: 99%
“…In the earlier works of neutrino-nucleus interaction of Refs. [25,26], the in-medium modification of the nucleon weak form factors was applied, but the effect of the in-medium EM form factors is yet to be explored. Certainly, one can expect that the in-medium nucleon EM form factors can influence the beta equilibrated matter composition as well as the neutrino-matter scattering cross sections.…”
Section: Medium Modification Of the Nucleon Weak And Electromagnetic ...mentioning
confidence: 99%
“…In previous studies of neutrino-nucleus scattering in Refs. [25,26], the authors, including one of us, estimated the (anti)-neutrino-nucleus scattering cross sections via charged [25] and neutral [26] currents for a bound nucleon by including the effect of the in-medium modified weak-magnetism and axial-vector form factors, F W 2 (q 2 ) and G A (q 2 ), respectively, where q is the transferred fourmomentum. (See e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent calculations [41,42] showed that differential cross sections for the neutrinoinduced reaction in 12 C by an ν E of less than 100 MeV may be altered by about 20-30% by the in-medium effect. In these calculations, we exploited the density-dependent weak form factors estimated in the quark-meson-coupling (QMC) model [43][44][45][46], which has been successfully applied in studying the properties of hadrons in nuclear matter, finite nuclei, and hypernuclei [47][48][49].…”
Section: Introductionmentioning
confidence: 99%